2007
DOI: 10.1016/j.vetmic.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of African swine fever viruses from outbreaks in southern Africa (1973–1999)

Abstract: African swine fever (ASF) is a highly lethal and economically significant disease of domestic pigs in the southern African sub-region, where outbreaks regularly occur. There is anecdotal evidence suggesting that trans-boundary movement of infected animals may have played a role in precipitating widespread outbreaks in the past, however, since the 1970s outbreaks have generally been more localised, particularly in those countries where control of animal movement is strictly regulated. The origin and relatedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(222 citation statements)
references
References 16 publications
6
209
2
5
Order By: Relevance
“…In addition, a homogeneous pigassociated lineage linked outbreaks that had occurred in Mozambique, Zambia and Malawi over a 23-year period. In southern Africa, a further six novel genotypes were identified based on sequencing of the B646L gene, bringing the total number to 22 (Boshoff et al 2007). As in East Africa (Lubisi et al 2005), some genotypes in southern Africa were countryspecific, while others had transboundary distributions (Boshoff et al 2007).…”
Section: Molecular Epidemiology Of African Swine Fever Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a homogeneous pigassociated lineage linked outbreaks that had occurred in Mozambique, Zambia and Malawi over a 23-year period. In southern Africa, a further six novel genotypes were identified based on sequencing of the B646L gene, bringing the total number to 22 (Boshoff et al 2007). As in East Africa (Lubisi et al 2005), some genotypes in southern Africa were countryspecific, while others had transboundary distributions (Boshoff et al 2007).…”
Section: Molecular Epidemiology Of African Swine Fever Virusmentioning
confidence: 99%
“…In southern Africa, a further six novel genotypes were identified based on sequencing of the B646L gene, bringing the total number to 22 (Boshoff et al 2007). As in East Africa (Lubisi et al 2005), some genotypes in southern Africa were countryspecific, while others had transboundary distributions (Boshoff et al 2007). These data have clearly demonstrated that greater genetic variation occurs where the sylvatic cycle is present and that occasional transmission occurs between the sylvatic and domestic cycle in addition to long-term circulation of conserved viruses within domestic pigs.…”
Section: Molecular Epidemiology Of African Swine Fever Virusmentioning
confidence: 99%
“…Variation in clinical disease and virus genome length and composition is known to occur, with infections in domestic swine ranging from sub-clinical to lethal and field strains having genomes up to 20 kbp longer than laboratoryadapted strains (Tulman et al, 2009). Recent molecular epidemiological studies have also uncovered substantial field heterogeneity with at least 22 genotypes being identified to date on the basis of C-terminus p72 gene sequencing (Bastos et al, 2003;Lubisi et al, 2005;Boshoff et al, 2007). The recent incursion of ASF into Georgia (Beltran Alcrudo et al, 2008;Rowlands et al, 2008) has highlighted the potential of the virus to expand its range towards Asia through the Caucasus and the Indian Ocean (Costard et al, 2009) as it encounters new populations of wild and domestic pigs, yet important gaps in our knowledge remain regarding the role of many wild Suidae in the maintenance of ASFV.…”
Section: Introductionmentioning
confidence: 99%
“…(Khomenko et al, 2013, Gulenkin et al, 2011, Lange et al, 2014. Bereits Ende 2012 wurden über 400 Ausbrüche bei Haus-und Wildschweinen in weiten Teilen der westlichen Russischen Föderation gemeldet (Khomenko et al, 2013 , Costard et al, 2009, Boshoff et al, 2007, Lubisi et al, 2007. Diese Genotypen sind oftmals auf bestimmte…”
Section: Epidemiologieunclassified
“…Dieser Genotyp kommt zurzeit endemisch in Mosambik, Sambia und auf Madagaskar vor , Costard et al, 2009) (Abbildung 3). Die verschiedenen Symbole stehen für die zirkuliernden Genotypen (basierend auf der B646L (p 72) Sequenzierung), soweit bekannt , Lubisi et al, 2007, Boshoff et al, 2007). …”
Section: Epidemiologieunclassified